2020
DOI: 10.29408/jpek.v4i2.2998
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Produk Domestik Bruto, Ekspor Dan Kurs Terhadap Cadangan Devisa Di Indonesia

Abstract: This study aims to analyze the effect of gross domestic product, exports and exchange rate on foreign exchange reserves in Indonesia. This research is in the form of quantitative based on quantitative data and is associative to see the relationship between variables or more. The data used is time series data from 2001 to 2018 using Eviews 9.0. And sourced from Bank Indonesia, the Central Bureau of statistics and the Federal Reserve Bank of St. Louis. This research uses data analysis technique is multiple linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
2
4
1
6
Order By: Relevance
“…The results of this study are in line with research conducted in Eswatini which revealed that foreign exchange reserves were driven by GDP as well as government spending (Khomo., et al, 2018). In addition, research conducted in GCC countries also states that GDP is one of the macroeconomic components that affects foreign exchange reserves (Azar & Aboukhodor, 2017), as well as other studies which state that GDP has a significant effect on foreign exchange reserves (Islami & Rizki, 2018;Astuty, 2020).…”
Section: T-statistic Testmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this study are in line with research conducted in Eswatini which revealed that foreign exchange reserves were driven by GDP as well as government spending (Khomo., et al, 2018). In addition, research conducted in GCC countries also states that GDP is one of the macroeconomic components that affects foreign exchange reserves (Azar & Aboukhodor, 2017), as well as other studies which state that GDP has a significant effect on foreign exchange reserves (Islami & Rizki, 2018;Astuty, 2020).…”
Section: T-statistic Testmentioning
confidence: 96%
“…In the long term, the exchange rate has an impact on foreign exchange reserves, as well as in the short term the exchange rate is also maintained its stability (Jena & Sethi, 2020). (Astuty, 2020). National income according to Keynes has a negative relationship to foreign exchange reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Adanya pengaruh yang mengarah positif akan tetapi tidak signifikan di dalam variabel produk domestik bruto secara parsial terhadap cadangan devisa di Indonesia periode triwulan tahun 2016-2020. Hal ini sesuai dengan penelitian yang dilangsungkan oleh (S & Zuhroh, 2018), (Astuty, 2020) dan (Indrayadi, 2017), dimana ketiga penelitian tersebut mampu mamaparkan bahwa peningkatan PDB mampu mempengaruhi cadangan devisa disebabkan volume transaksi internasional yang turut meningkat. Adanya peningkatan di dalam tiaptiap komponen PDB, seperti keperluan konsumsi rumah tanggan, konsumsi pemerintah, investasi, dan ekspor akan mengakibatkan jumlah PBD turut meningkat.…”
Section: Pengaruh Produk Domestik Bruto Terhadap Cadangan Devisa DI Indonesiaunclassified
“…Komponen dari Produk Domestik Bruto ialah bahan yang dikonsumsi bagi sebagian besar rumah tangga, investasi, konsumsi pemerintah, dan ekspor neto. Semua komponen yang telah disebutkan tersebut terletak ke dalam sebuah fungsi linier, dapat ditarik sebuah simpulan bahwa meningkatnya Produk Domestik Bruto yang dimiliki sebuah negara akan mempengaruhi peningkatan cadangan devisa begitupun sebaliknya (Astuty, 2020).…”
unclassified
See 1 more Smart Citation